The Effect of Extracurricular Activities on Generate Motivation for Learning Physics Students Practical Study on Secondary Students in Public Schools in Karak Province - Al-qatawneh, Eman Mohammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the effect of extracurricular activities on raising the motivation of learning among physics students in the tenth grade in government schools in Karak Governorate, where the study followed the descriptive research methodology, and the experimental research methodology of two groups, control and experimental, which included 30 students in each group, where they were Pre and post testing for the two groups. The experimental group was subjected to a program that included extracurricular activities through sports, games, art, music, drama and poetry. The control group was not subject to these activities. The study concluded that there is high important level of extracurricular activities in the motivation of students of physics at the Tenth grade in public schools in Karak Governorate. And there is a significant impact of extracurricular activities on raising the motivation of learning among students of physics at the Tenth grade in public schools in Karak Governorate. In light of the results, the study recommended the need to apply extracurricular activities to students of physics at the Tenth grade in public schools in Karak Governorate.